Self-determined motivation, emotional process and subjective performance among young elite athletes: A longitudinal hierarchical linear modelling approach - Cece, V.; Duchesne, M.; Guillet-Descas, E.; Martinent, G. (European Journal of Sport Science, 2020)
This study aimed to explore relationships between contextual self-determined motivation, everyday appraisals and emotions related to the competitive environment and subjective performance of young elite athletes. Thirty-one young tennis players (18.45 years ± 4.63) involved in intensive training centres completed initial (Time 0 - T0) self-determined motivation questionnaire and a fortnightly logbook including everyday cognitive appraisals, discrete emotions and subjective performance. We computed a series of hierarchical linear modelling analyses (HLM) to explore the relationships between the variables and Sobel tests to examine the mediating effects. HLM results showed that: (a) T0 autonomous motivation was positively associated with adaptive appraisals (challenge and benefits); (b) threat and loss were positively related to unpleasant emotions (anxiety, anger, dejection) and negatively associated with pleasant emotions whereas challenge and benefits were positively related to pleasant emotions and negatively associated with unpleasant emotions; (c) subjective performance was positively associated with happiness and negatively associated with dejection. Moreover, the Sobel tests revealed that: (a) appraisal was a mediator of the relationship between T0 self-determined motivation and discrete emotions; and; (b) emotions were mediators of the relationship between appraisals and subjective performance. In sum, the present study showed that young athletes` self-determined motivation assessed at the beginning of the study impacted their everyday cognitive appraisals, their experience of pleasant and unpleasant emotions, and their subjective performance levels along a 4-month period. To conclude, this study highlighted the relationships between the self-determined motivation, the emotional process and the performance of young elite athletes involving in intensive training settings.